Designing polymer nanocomposites with a semi-interpenetrating or interpenetrating network structure: toward enhanced mechanical properties. Issue 24 (1st June 2017) - Wang, Wenhui; Hou, Guanyi; Zheng, Zijian; Wang, Lu; Liu, Jun; Wu, Youping; Zhang, Liqun; Lyulin, Alexey V.
Abstract : Semi-interpenetrating and interpenetrating network structures for the uniform dispersion of NPs and the reinforced mechanical properties of polymer nanocomposites. Abstract : Using short polymer chains and through molecular dynamics simulation, we designed a well-dispersed nanoparticle (NP) network, which was then incorporated with the polymer matrix. First, we examined the effects of the dual-end grafted chains flexibility and density on the spatial distribution of this particular polymer nanocomposites system. By changing the interaction strength between the matrix polymer chains and the dual-end grafted chains in the semi-interpenetrating network system (NP network), we analyzed the interpenetration state between the linear polymer matrix and the NP network via calculating the total interfacial interaction energy. Moreover, the uniaxial tensile stress–strain and orientation behavior influenced by the interaction strength between the matrix polymer and the grafted chains were investigated for both the semi-interpenetrating network system and the interpenetrating network system (NP network and matrix network). Furthermore, for the interpenetrating network system, we modulated the integrity of the NP network ranging from 0% to 100%, corresponding to the gradual transition of the dispersion morphology of the NPs from the aggregation state to the uniform dispersion state, to examine the effect of the NP network on the tensile mechanical behavior. In particular, by simulating the dynamic shear process in the semi-interpenetrating network system, the composites were found to exhibit a lower non-linear behavior (the famous Payne effect), a higher storage modulus, and a lower tangent loss at large strain amplitude with increasing NP network integrity. In general, our results could provide a new approach for the design of high-performance polymer nanocomposites by taking advantage of the semi-interpenetrating or interpenetrating network reinforcing structure.